MOTIVATIONAL REASONS AND MUZAKI INTENTION TO PAY THROUGH ZAKAT INSTITUTIONS - Junaidi Junaidi; Eka Meirawati; Titin Vegirawati (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
This study examined motivational factors that influence Muzaki intention to pay zakat through Zakat Institutions. Paying zakat through Zakat Institutions will reduce poverty and increase economic growth. This research combines theory of intention revision and Signaling Theory. From those theories, this research utilized website quality, service quality, and Zakat Institutions performance which are suspected influence muzaki intention to pay. Purposive sampling was applied to obtain 100 qualified respondents that answered the questionnaires. The primary data were analyzed using a multiple regression model. Based on the research results, proposed hypotheses were accepted. Motivational reasons that contain website quality, service quality, and Zakat Institutions management performance have proven influence muzaki intention to pay zakat through Zakat Institutions. These research results suggest to Zakat Institutions and zakat authorities to give attention on motivational reasons variables. They should improve the role of each variable to attract muzaki intention to pay zakat